Comparing efficacy of schema therapy & emotion-oriented therapy on adherence to treatment in patients with MS - Azita Mohaghegh; Biuok Tajeri; hadi keramati (مجله علوم روانشناختی, 2025)
Background: Low treatment adherence in patients with MS leads to poor treatment outcomes and higher care costs. Studies have reported on the effect of schema therapy to improvement adherence to treatment, also, emotion-oriented therapy by empowering effect on this. However, compares the effect these in patients with MS has been overlooked. Aims: the aim of this syudy is to compare the efficacy of schema therapy & emotion-oriented therapy on adherence to treatment in patients with MS. Methods: Research method was quasi-experimental with pre-test, post- test, three-month follow-up with control group. The statistical population consist of all patients suffering from MS who in the second half of 2020 referred to the Iranian MS Association to receive services in Tehran. Sampling method was Purposful. 60 available patients selected (twenty in each experimental group) and replaced randomly in experimental groups. twenty other patients placed in control group and did not receive any training. The adherence to treatment Inventory (seyd fatemi et al., 2018) was administered pre-test, post-test and follow-up. Packages were schema therapy package (Young et al, 2016) and emotion-oriented therapy package (Gilbert & Goldman, 2019). Both applied on experimental groups (sixty minutes each session) weekly and the control group did not receive any therapy. The data analyzed by mixed analysis variance and SPSS. Results: Results showed that both of schema therapy & emotion-oriented therapy were affected the same on increasing to adherence to treatment (p< 0.001). Three- month follow-up confirmed these results. Use to schema therapy & emotion-oriented therapy (especially schema therapy) can to increase to adherence to treatment in patients with MS. Conclusion: With the two methods of schema therapy and emotion-oriented therapy, it is possible to improve treatment compliance in MS patients. The mentioned findings can help therapists in choosing the type of treatment in these patients.